Analisis Regresi Nilai Kekuatan Mekanik Biomaterial Cangkang Kerang Darah Dan Resin Akrilik Bahan Gigi Tiruan - Afrizal; Eko Martono; Donny Setiawan (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2024)
Extruded biomaterials made from clamshell have the potential to reduce the reliance on imported materials to make dentures, however, clamshell biomaterials and Acrylic Resin have no known effect as denture mix materials, so their effect as a denture mix material needs to be studied. using regression analysis. Multiple Linear Regression where a dependent variable (Variable Y) is associated with two or more independent variables (Variable X). Variables. Variables Variables Variables The effects of testing the compressive strength and flexural strength of blood clam skin biomaterial with acrylic resin alloy have no significant or dominant influence on either blood clam skin biomaterial powder or acrylic resin but both have an influence as replacement materials for denture composites. whose basic material is expensive acrylic resin. price.